Modelling And Analysis Road Energy Harvester Using Piezoelectric Tranducer - Mazlan, Mazwin; Hazlami Abd Manan, Mohamad; Fairuz Mohamed Yusof, Nur (International Journal of Engineering and Technology, 2019)
This paper describes the design of energy harvester from the road using piezoelectric transducer for creating a clean energy source without disturbing any existing ecosystem. The clean energy source is not only able to sustain the well-being of the environment, but is also recognized as a renewable energy source comparable to the energy sources generated by solar energy, wind, biomass and others. This study is intended to answer the fundamental question for design energy harvesters using Proteus Software. In this paper, the piezoelectric sensors are used as a key element in generating electricity. Piezoelectric sensors that conduct for converting kinetic energy to electricity have placed vibrations from the movement of vehicles and humans as the main focus of the project. Simulation by Proteus Software is used to determine the best circuit connection for converting an alternative current (AC) to direct current (DC). Comparison of voltage doubler and rectifier circuit is applied to obtain better voltage output. Furthermore, designing a model that required the road energy harvesting characteristics is implemented to validate the analysis of two different sources which are vehicle and walking people vibration. As a result, an output voltage produce by 4 Series 2 Parallel circuit connection for voltage doubler is selected with contribute 6.634 V at maximum setting frequency.Â